The evolutionary dynamics of organellar pan-genomes in Arabidopsis thaliana - Yi Zou; Weidong Zhu; Yingke Hou; Daniel B. Sloan; Zhiqiang Wu (Genome Biology)
Abstract Background In plants, comparative analyses of organellar genomes are often based on draft assemblies. Large-scale investigations into the complex structural rearrangements of mitochondrial genomes remain scarce. Results Here, we perform a comprehensive analysis of the dominant conformations and dynamic heteroplasmic variants of organellar genomes in the model plant Arabidopsis thaliana, utilizing high-quality long-read assemblies validated at high resolution from 149 samples. We find that mitochondrial and plastid genomes share common types of structural and small-scale variants driven by similar DNA sequence features. However, rearrangements mediated by repetitive sequences in mitochondrial genomes evolve so rapidly that they are often decoupled from other types of variants. Rare complex events involving elongation and fusion of existing repeats are also observed, contributing to the unalignable regions commonly found at the interspecies level. Additionally, we demonstrate that disrupting and rescuing organellar DNA maintenance could drive the rapid evolution of dominant mitochondrial genome conformations. Conclusions Our study provides an unprecedentedly detailed view of the dynamics of organellar genomes at pan-genome scale in Arabidopsis thaliana, paving the way to unlock the full potential of organellar genetic resources.